Inklusiver Unterricht in der Grundschule

Human agency at work: An active approach towards expertise development - Goller, Michael
Michael Goller gives a structured overview of the current discourses of human agency in relation to professional learning and development. Based on this discussion, the author develops a theoretical framework including human agency as an individual feature (i. e., a disposition) as well as a set of self-initiated and goal-directed behaviours that are assumed to affect employees’ learning and development (e. g., crafting of new work experiences). He then further specifies this theoretical framework and investigates it empirically in the domain of geriatric care nursing. Based on the findings of the three empirical studies conducted, the author discusses the relevance of human agency for the development of professional expertise of geriatric care nurses. The work received the American Educational Research Association (AERA) Workplace Learning SIG 2017 Dissertation of the Year Award.
Keywords: Workplace learning; Agency; Expertise

Intuition as Crucial Component of Professional Competence: Its Relevance for Competence-based Vocational and Professional Education and Training - Harteis, Christian (Competence-based Vocational and Professional Education)

Emotions, coping and learning in error situations in the workplace - Rausch, Andreas; Seifried, Jürgen; Harteis, Christian (Journal of Workplace Learning)

Human agency at work: Towards a clarification and operationalisation of the concept - Goller, Michael; Harteis, Christian (Agency at Work)

Learning from errors in workplace settings - Harteis, Christian; Gartmeier, Martin (Journal of Workplace Learning)

Epistemische Überzeugungen Beschäftigter und ihre Bedeutung für berufliches Lernen - Harteis, Christian; Festner, Dagmar; Bauer, Johannes (Wissen und Lernen. Wie epistemische Überzeugungen Schule, Universität und Arbeitswelt beeinflussen)

Digitalisierung in der Schule (Lernende Schule)

Multiprofessionelle Kooperation in der Schule: Forschungsbefunde und Handlungsperspektiven für Schulleitungen - Drossel, Kerstin; Gröhlich, Carola (Schulmanagement)

Predictors of Teachers’ Use of ICT in School – the Relevance of School Characteristics, Teachers’ Attitudes and Teacher Collaboration - Drossel, Kerstin; Eickelmann, Birgit; Gerick, Julia (Education and Information Technologies)

Determinants of teachers’ collaborative use of information and communications technology for teaching and learning: A European perspective - Drossel, Kerstin; Eickelmann, Birgit; Schulz-Zander, Renate (European Educational Research Journal)

Rezension des Buches von Jasmin Bastian und Stefan Aufenanger: Tablets in Schule und Unterricht. Forschungsergebnisse zum Einsatz digitaler Medien - Drossel, Kerstin (Journal für Schulentwicklung)

Teachers’ participation in professional development concerning the implementation of new technologies in class: a latent class analysis of teachers and the relationship with the use of computers, ICT self-efficacy and emphasis on teaching ICT skills - Drossel, Kerstin; Eickelmann, Birgit (Large-scale Assessments in Education)

Digitale Bildung – ein neue Perspektive auf Bildungsgerechtigkeit? - Eickelmann, Birgit; Drossel, Kerstin (Dreizehn - Zeitschrift für Jugendsozialarbeit)

Computer- und informationsbezogene Kompetenzen in der IEA Studie ICILS 2013 und der Zusammenhang mit der Lesekompetenz - Eickelmann, Birgit; Drossel, Kerstin (Medienimpulse)
Der kompetente Umgang mit Informations- und Kommunikationstechnologien (ICT) gewinnt im Zuge des Wandels zur Informations- und Wissensgesellschaft zunehmend an Bedeutung. Die International Computer and Information Literacy Study (ICILS 2013) erfasst in diesem Zusammenhang erstmals computer- und informationsbezogene Kompetenzen computerbasiert im internationalen Vergleich. Theoretische Überlegungen und empirische Befunde postulieren dabei einen Zusammenhang der erfassten Kompetenzdomäne mit der Lesekompetenz der Schülerinnen und Schüler. Eine empirische Untersuchung dieses Zusammenhangs steht bislang allerdings noch aus und ist das Anliegen dieses Beitrags. Um diesem Desiderat nachzugehen, werden die repräsentativen Schülerdaten aus ICILS 2013 für Deutschland herangezogen. Dabei wird die Untersuchung des Zusammenhangs der beiden Konstrukte möglich, da in Deutschland national ein Lesetest ergänzt wurde, den die Achtklässlerinnen und Achtklässler zusätzlich bearbeitet haben. Die Pfadanalyse zeigt, dass Lesen einen mittleren direkten Effekt von .452 auf die computer- und informationsbezogenen Kompetenzen aufweist.

The Use of Tablets in Secondary Schools and Its Relationship with Computer Literacy - Drossel, Kerstin; Eickelmann, Birgit (Tomorrow's Learning: Involving Everyone. Learning with and about Technologies and Computing)

Die Bielefelder Längsschnittstudie zum Lernen in inklusiven und exklusiven Förderarrangements (BiLieF) - Neumann, Phillip; Lütje-Klose, Birgit; Wild, Elke; Gorges, Julia (Schulische Inklusion und Übergänge)
Keywords: BiLieF

"Es sind erstmal Kinder...": Inklusion im Kontext von Kindern und Familien mit Fluchterfahrungen - Albers, Timm; Ritter, Charlotte Eva (Multiprofessionelle Perspektiven auf Inklusion)
Keywords: s2n; Scan2Net

Brücken ins Bildungssystem? - Niedrigschwellige Angebote zur Integration von Kindern und Familien mit Fluchterfahrung - Albers, Timm; Hoeft, Maike (Gemeinsam leben)

Sprachliche Bildung und Förderung im Kontext von Inklusion. Grundlagen und Perspektiven einer inklusiven Frühpädagogik. - Albers, Timm (Professionalisierung in der Frühpädagogik)